Poultry breeding center combines science and art - Clements, M. (WATT Global Media, 2018)
A new poultry breeding facility in Ethiopia aims to improve rural nutrition and incomes, produce birds that are more disease resistant, and bring art to the local farming community as part of efforts to improve understanding of the importance of genetic diversity. Incubated Worlds, as the facility is known, aims to produce chickens that have the genetic diversity to survive disease and adapt to climate change, while still producing food for farmers. It has come about as part of the African Chicken Genetic Gains (ACGG) project, established in 2014 to tap the genetic diversity found in poultry and to provide more opportunities for rural producers. But why include art? Reaching farmers While the primary aim of the center is to improve chickens, its developers feel that the art element can educate in a way that science alone never could. This additional dimension is being fulfilled through working with Belgian artist Koen Vanmechelen who, throughout the past two decades, has created 20 generations of chickens that combine traits from breeds from around the world. This cross-breeding project has resulted a bird that Vanmechelen calls the “Cosmopolitan Chicken,” and which is said to be a treasure trove of traits. The art installation component of Incubated Worlds includes photographs, videos and books offering insight into the complex genetics of Vanmechelen’s work and of Ethiopian chickens. Dual aspect In preparations for the opening, International Livestock Research Institute (ILRI) geneticists worked with the Ethiopian Institute of Agricultural Research to import and hatch several of Vanmechelen’s chickens, which will be crossed with the indigenous chickens preferred by local farmers to create what has been called the “Ethiopian African Planetary Chicken.” ILRI director Jimmy Smith has said the center will develop productive, resilient poultry for a part of the world where demand for livestock products is rising rapidly while climate change is undermining agricultural diversity. He continued that combing the research center with Vanmechelen’s art installation conveyed the importance of livestock genetic diversity in ways that science alone simply could not. The center is hoping to broaden, replenish and conserve the genetic base of Ethiopian chickens, and the genomes of both birds have been sequenced by scientists who, with the artist, are aiming to offer the public a greater appreciation of the importance of genetic diversity. The facility will help scientists in Ethiopia and elsewhere monitor, understand and apply genetic technologies to improve chicken breeds smartly and quickly, while also working with farmers’ associations to encourage more efficient breeding, feeding and husbandry practices to develop and grow poultry businesses.